EMERGENCY MANAGEMENT OF HEMORRHAGIC CYSTITIS IN MALE DOMESTIC CAT: A CASE REPORT - I Made Adi Brahmantika; Ida Ayu Dian Kusuma Dewi; I Putu Gede Yudhi Arjentinia (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
An emergency is a condition that requires rapid and appropriate action to prevent a situation that can guarantee safety. This condition occurred in a 2-year-old local male cat that had not been spayed and presented with extreme weakness, dysuria, oliguria, and decreased consciousness with a very weak body response. Physical examination showed a tense bladder palpation, slow skin turgor, dry mucosa, tachycardia, and weak pulse, indicating an emergency condition due to dehydration and possible urinary tract obstruction. Supporting examinations included urinalysis, SDMA, hematology, and ultrasound. Results showed an alkaline urine pH, struvite crystals, a positive urease bacterial infection, and hyperechoic material in the bladder. The patient was diagnosed with hemorrhagic cystitis with a questionable prognosis. Treatment consisted of stabilizing the patient's condition using warmers and Ringer's Lactate infusion fluid therapy, followed by drug therapy using the antibiotic ciprofloxacin for 14 days, acidifying with Acidurin for 7 days, supportive care with Cystaid for 14 days, ipakitine for 7 days and changing the feed to WetFood for the Urinary Tract. The results of the therapy showed positive results, with the patient's condition improving. Prevention of urinary tract disorders is done by maintaining cleanliness, ensuring adequate water intake, providing special food, and immediately consulting a veterinarian if there are symptoms of difficulty urinating.